THE UNCODIFIED HADITH (Study on the Hadith Narration by ‘Abdullah Ibn Amru Ibn al-ʻAṣ) - Fahrizal Mahdi (Jurnal Ushuluddin, 2018)
This article is inspired by the words of Abû Hurairah mentioning the number of hadiths Abdullah ibn ‘Amru received is more than what he acquired, considering he [Abdullah] had the luxury of writing everything he heard from Prophet Muhammad and the result of his writing has become a masterpiece called al-Ṣahîfah al-Ṣâdiqah. In fact, the number of the hadiths received by Abdullah which are codified are very limited, whereas the number of hadiths narrated by Abû Hurairah in the hadith books written by scholars such as al-Jawâmi’, al-Masânid, al-Sunan and others have bigger proportion. No wonder if he was known as a friend who narrated the hadiths the most. This article aims at examining the reason this could happen. As the result, it concludes the less number of hadiths Abdullah received is due to domicile factor which was not the main destination for hadith seekers and personal factor in which he spent most of his time for worship and anticipated other scholars not to narrate israiliyat. In addition, the hadiths narrated by Abû Hurairah did not all refer to the Prophet, but received from his companions